2020
DOI: 10.1186/s12711-020-00547-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of whole-genome sequence data and novel genomic selection strategies to improve selection for age at puberty in tropically-adapted beef heifers

Abstract: Background: In tropically-adapted beef heifers, application of genomic prediction for age at puberty has been limited due to low prediction accuracies. Our aim was to investigate novel methods of pre-selecting whole-genome sequence (WGS) variants and alternative analysis methodologies; including genomic best linear unbiased prediction (GBLUP) with multiple genomic relationship matrices (MGRM) and Bayesian (BayesR) analyses, to determine if prediction accuracy for age at puberty can be improved. Methods: Genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Therefore, many approaches were proposed to identify the truly candidate variant from hundreds of significant variants with the high levels of LD, including condition and joint analysis ( Yang et al, 2012 ) and Bayesian fine-mapping ( Jiang et al, 2019 ). These strategies have been applied to precisely identify the causal variants and capture the secondary association signals for economically important traits in cattle ( Fang et al, 2019 ; Freebern et al, 2020 ; Sanchez et al, 2020 ; Warburton et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many approaches were proposed to identify the truly candidate variant from hundreds of significant variants with the high levels of LD, including condition and joint analysis ( Yang et al, 2012 ) and Bayesian fine-mapping ( Jiang et al, 2019 ). These strategies have been applied to precisely identify the causal variants and capture the secondary association signals for economically important traits in cattle ( Fang et al, 2019 ; Freebern et al, 2020 ; Sanchez et al, 2020 ; Warburton et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such methods include using Bayesian derived SNP effects to better estimate the distribution of effects, and incorporating more SNP into the prediction, rather than imputing to whole genome sequence and then sub sampling back to 641,000 SNPs. Both these methods have been shown to slightly increase prediction accuracies [40,41] and would add little computational time once the SNP effects are calculated.…”
Section: Discussionmentioning
confidence: 99%
“…In Nellore cattle, accuracies ranging from 0.23 to 0.63 were reported for age first calving [ 83 , 84 ] and from 0.25 to 0.67 for heifer early pregnancy, respectively [ 84 , 85 ]. Evaluations of age at puberty in Brahman and Tropical Composite indicated prediction accuracies varying between 0.20 and 0.50 [ 8 , 17 , 86 ]. Differences in terms of reference population size, study design, population structure, among others, explain this high predictive ability variation among studies.…”
Section: The Genetics Of Heifers Sexual Precocitymentioning
confidence: 99%
“…Recently, Warburton et al [ 86 ] showed that genomic predictions for age at puberty in tropically-adapted beef heifers could benefit from the use of WGS data. The general idea is to add preselected WGS variants using genome-wide association study to a regular SNP array [ 90 ].…”
Section: The Genetics Of Heifers Sexual Precocitymentioning
confidence: 99%
See 1 more Smart Citation